PENGENALAN EDUKASI GERAKAN DAN BACAAN SHALAT WAJIB BERBASIS ANDROID - Wibowo, Sigit Tri; Hariyono, Rito Cipta Sigitta; Aeni, Khurotul (Smart Comp :Jurnalnya Orang Pintar Komputer, 2020)
Prayer is the main pillar of religion and worship in the religion of Islam, the ruling on prayer is obligatory for all Muslims. In the procedure for working on the prayer movement must be orderly and in accordance with the way that has been determined. In this paper, we will discuss the process of making the application of movement learning and reading the obligatory prayers. This theme was raised because of the interest of children (aged 5-7 years) in the village of Prupuk Selatan RT 02 RW 03 still lacking in learning about the obligatory prayer guidelines. Parents usually provide movement learning and prayer recitation to their children still using conventional media such as books, brochures and the like. The purpose of this study was to produce a 3D educational application of compulsory prayer and reading prayers based on android with system design methods using the waterfall method. The results of the design of 3D motion education applications and prayer readings must display the animation of the prayer movement must be accompanied by the sound of reading, this educational application was successfully built with the developer tools 3DS Max 2012 and Unity 3D.Â Kata kunci : Shalat, Unity 3D, Animasi 3D, 3DS Max